Augmented Reality Teknik Informatika Stt-Pln Berbasis Android - Yessy Asri; Lukman Hakim (KILAT, 2016)
This app uses Augmented Reality technology, 3D animations and use android smartphone devices. 3D information can be obtained through the android camera directed at the magazine marker. In this apliaksi there are features that help the user to obtain information related to informatics engineering majors such as class layout, organizational structure, video etc.